World Bank Group Sanctions Board Law Digest 2019 - World Bank Group Sanctions Board (Washington, DC: World Bank, 2019)
This edition of the Law Digest for the World Bank Group's Sanctions Board presents structured summaries of the Sanctions Board's precedent as set out through more than 100 decisions issued since 2007. The Law Digest also includes key data relating to the work of the Sanctions Board and the World Bank Group's larger sanctions system. Themes covered in this digest include the scope of the Sanctions Board's authority, various types of procedural and evidentiary questions in sanctions proceedings, and the Sanctions Board's overall analysis of the allegations of fraud, corruption, collusion, and obstruction in projects supported by the World Bank Group that form the core of individual sanctions cases.